Analisis Hidup Selaras Alam pada Masa Kini Refleksi Teologis: Kejadian 2:15 - Mega Intan Tambunan; Sisga Desriman Zebua (Jurnal Pendidikan Agama dan Teologi, 2024)
Human survival depends on maintaining the balance of the ecosystem. The government and the community must work together in terms of land clearing that occurs continuously which makes living things lose their homes. By maintaining and preserving nature as well as possible, Christians who understand the importance of this should be a driving force in the preservation of nature and the environment which is also written in Genesis 2:15. The method used in this research is a qualitative method. The research approach used to understand complex and contextual phenomena by delving into the meanings, experiences, and views of individuals or groups. Theological reflection based on Genesis 2:15 on how to live in harmony with nature offers deep insights into human responsibility for the environment. It is the foundation for a sustainable future, where humans can live in harmony with their environment, maintain the balance of the ecosystem, and ensure well-being for all living beings.